Case Report: A Possible Case of Congenital Erythropoietic Porphyria in a Gir Calf: A Clinical, Pathological, and Molecular Approach - Queiroz, Cintia Regina Rêgo; Machado, Mizael; Bromberger, Cristiana Raach [UNESP]; Oliveira-Filho, Jose Paes [UNESP]; Borges, Alexandre Secorun [UNESP]; Soto-Blanco, Benito; Borges, José Renato Junqueira; Câmara, Antônio Carlos Lopes; Castro, Márcio Botelho de (Frontiers, 2021)
Congenital erythropoietic porphyria (CEP) is a rare hereditary autosomal recessive disease which has never been reported in Zebu cattle. A 3-day-old Gir calf showed teeth discoloration, fever, dehydration, and dyspnea. The main gross findings were pink-colored teeth, red-brown periosteum and bone marrow, and a fluorescent bright pink coloration of the bone marrow and articular surfaces under ultraviolet light. Aggregates of periodic acid-Schiff (PAS)-stained porphyrin pigments were evident in the lungs, kidneys, and the liver. An intron 8 single-nucleotide polymorphism (SNP) in both the Gir calf and control animals, along with the absence of the uroporphyrin III synthetase (UROS) gene mutation, was observed. Most SNPs were located in the intron regions of the UROS gene without relevance for CEP. A continuous loss of genetic variability and an increase in inbreeding in some herds may be related to CEP in Gir cattle, one of the most prominent Zebu breeds worldwide. In summary, this study describes a presumptive case of CEP in a Gir calf based on clinical and pathological findings. A definitive diagnosis would require the measurement of porphyrin levels in blood, urine, or tissues or the identification of UROS gene defects.
Keywords: cattle; pink teeth; porphyrin; uroporphyrin; Zebu